2020
DOI: 10.1101/2020.12.11.20246546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Learning Fusion for COVID-19 Diagnosis

Abstract: The outbreak of the novel coronavirus (COVID-19) disease has spurred a tremendous research boost aiming at controlling it. Under this scope, deep learning techniques have received even more attention as an asset to automatically detect patients infected by COVID-19 and reduce the doctor’s burden to manually assess medical imagery. Thus, this work considers a deep learning architecture that fuses the layers of current-state-of-the-art deep networks to produce a new structure-fused deep network. The advantages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…The results showed that the classification accuracy of this model was 99.08% in the multi-classification task and the classification accuracy of 99.53% in the binary classification task. Kechagias-Stamatis et al [121] proposed a new structure-fusion deep learning network, which integrated the layers of GoogleNet and ResNet18. In addition, they evaluated the model in two experiments, binary classification, and multi-classification.…”
Section: Covid-19 Diagnosis Based On Ensemble Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the classification accuracy of this model was 99.08% in the multi-classification task and the classification accuracy of 99.53% in the binary classification task. Kechagias-Stamatis et al [121] proposed a new structure-fusion deep learning network, which integrated the layers of GoogleNet and ResNet18. In addition, they evaluated the model in two experiments, binary classification, and multi-classification.…”
Section: Covid-19 Diagnosis Based On Ensemble Learningmentioning
confidence: 99%
“…The accuracy of the proposed network was 99.08% in the multi-classification task and 99.53% in the binary classification task. Kechagias-Stamatis et al [121] X-ray, CT GoogleNet, ResNet18, a structure-fusion deep learning network The classification capability of the structure-fusion deep learning network was evaluated on CT and X-ray datasets with 99.30% and 100.00% classification accuracy, respectively.…”
Section: Gupta Et Al [120]mentioning
confidence: 99%
“…The classification of COVID-19 and pneumonia seeks to separate patients infected with SARS-CoV-2 from those with pneumonia caused by another agent [7,[42][43][44][45][46][47][48][49][50]. The classification of COVID-19 and non-COVID-19 seeks to distinguish patients diagnosed with infection caused by SARS-Cov-2, from those that present characteristics of classic pneumonia, healthy or with a diagnostic of other lung diseases [51][52][53][54][55][56][57][58][59][60]. In addition, some works presented different methodologies [7] that are able to detect the lesion of the image indicating its severity.…”
Section: Covid-19 Detection Based On Computed Tomographymentioning
confidence: 99%